Andrew Shorten’s Multiculturalism: The Political Theory of Diversity Today - Durgut, Hasene (Central European Journal of Educational Research, 2025)
Bibliography of the reviewed book: Shorten, A. (2022). Multiculturalism: The political theory of diversity today. Polity Press.